KOMPARASI ANALISIS KELAYAKAN USAHATANI PENANGKARAN BENIH PADI DAN USAHATANI PADI KONSUMSI DI PROVINSI SULAWESI TENGAH - Muhammad Iqbal; Muhammad Afif Juradi (Universitas Sebelas Maret, 2015)
The existence of rice farming can be generally classified into two-category, namely rice farming for breeding and rice farming for consumption. This article aims at: (1) identifying and describing the rice farming; (2) analyzing the feasibility of rice farming for breeding and consumption; and (3) formulating the development policy of rice farming for breeding and consumption in the locale of the study (Central Sulawesi province). The research result shows that the extent of feasibility of rice farming for breeding (RCR=1.80) was higher than that of rice farming for consumption (RCR=1.67). Even though the rice farming for breeding was prospective, the sustainability of this rice farming activity would be depended upon demand from farmers and other users, the existing government program, and financial investment capacity of rice farmer breeders. Hence, assuring the demand and providing the favorable price of rice seeds are two important aspects supporting the continuity of rice farming for breeding includes rice farming for consumption in the province of Central Sulawesi.